Concept-guided development of technology in 'traditional' and 'innovative' schools: quantitative and qualitative differences in technology integration - de Koster, Sandra; Volman, Monique; Kuiper, Els (Educational technology research and development, 2017)
The integration of technology into the classroom remains a challenge for those involved. A concept-guided approach to the development of technology has been suggested as a way of meeting this challenge. This multiple case study was performed in the context of a project in which five elementary schools in The Netherlands with a school concept that was labeled as either 'traditional' or 'innovative' developed and realized up to four technology-supported learning arrangements in line with their schools' educational concepts. Through embedded case studies, including analysis of the learning arrangements and focus group interviews with the teachers involved, we found that in general the developed technology use became integrated in the teachers' classroom practices at all schools to a similar extent. Some differences were found between the schools, but hardly any were found between the school types. Both practical and theoretical implications of these findings are discussed.